Natural convection in a porous enclosure with a partial heating and salting element - Zhao, Fu-Yun; Liu, Di; Tang, Guang-Fa (International journal of thermal sciences, 2008)
This paper reports a numerical study of double-diffusive convective flow of a binary mixture in a porous enclosure subject to localized heating and salting from one side. The physical model for the momentum conservation equation makes use of the Darcy–Brinkman equation, which allows the no-slip boundary condition on a solid wall to be satisfied. The set of coupled equations is solved using the SIMPLE algorithm. An extensive series of numerical simulations is conducted in the range of − 15 ⩽ N ⩽ + 14 , 10 −3 ⩽ Le ⩽ 10 2 , 10 −8 ⩽ Da ⩽ 10 2 and 0.125 ⩽ L ⩽ 0.875 , where N, Le, Da and L are the buoyancy ratio, Lewis number, Darcy number and the segment location. Results for a pure viscous fluid and a Darcy (densely packed) porous medium emerge from the present model as limiting cases. Streamlines, heatlines, masslines, isotherms and iso-concentrations are produced for several segment locations to illustrate the flow structure transition from solutal-dominated opposing to thermal dominated and solutal-dominated aiding flows, respectively. The segment location combining with Lewis number is found to influence the buoyancy ratio at which flow transition and flow reversal occurs. The computed overall Nusselt and Sherwood numbers provide guidance for locating the heating and salting segment.